Dismantling white supremacy through anti-racist and decolonial pedagogies: Mapping postsecondary education’s capacity for shifting dynamics of privilege and marginalization - Ma, J.; Maradiaga Rivas, V.; Huang, X.; Khan, M.; Rukh E Qamar, H.; Salih, A.; Esemu-Ezewu, J.; Satia, A.; Joseph, A.; Gabel, C.; Saravanamuttu, K.; Bent-Womack, C. (My University, 2023)
Generally, in post-secondary education there is growing discourse around decolonizing the academy and anti-racist movements with little tangible follow through. This knowledge synthesis seeks to respond to the contradictions within theory, pedagogy and practice that are complicit with and perpetuate systemically racist outcomes in the world. The findings demonstrate that the main characteristics across anti-racist and decolonial pedagogies include: decentering dominant discourses, disrupting hierarchical power relations, relationality, reflexivity, intentionality, and creativity. Furthermore, white supremacy, whiteness, settler colonialism, and racism must be named and discussed with the intent of dismantling systems of oppression. Universities need to shift from performative, surface level changes to structural and systemic change supporting implementation while participating in accountability processes. Decolonial thought, anti-racist scholarship and activism, critical race theory, and anti-oppressive discourses have all contributed to transforming post-secondary education. These findings will inform public and educational policy, promoting a truly decolonial and anti-racist learning environment, enhancing participation, representation, and knowledge sharing within the academy and society at large.
Final report submitted to SSHRC as required by the SSHRC Knowledge Synthesis Grant
Keywords: Anti-racist pedagogies; decolonial pedagogies; post secondary education; systemic racism